Medieval Yeghegis, Armenia - Pogossian, Zaroui (ED); Nucciotti, Michele (ED) (Masarykova univerzita, 2026)
This collective volume explores the rich history and archaeological heritage of Yeghegis, a modest village nestled in the Vayots'Dzor region of Armenia, historically a part of the Syunik'province. By examining its multifaceted past, the book underscores Yeghegis'pivotal role as a nexus within medieval networks of political authority, as well as cultural and commercial exchanges, shedding light on its importance in the broader socio-economic landscape of the period between the 9th and 14th centuries. The pioneering articles in the collection provide a comprehensive study of Yeghegis'splendid material cultural legacy through the application of archaeological, stratigraphic methodologies for the first time, as well as through the lens of archaeology of production and ‘light archaeology'. By integrating perspectives from the broader framework of the medieval global context with a meticulous analysis of local (including inter-dynastic) dynamics, the research redefines Yeghegis'role as a ‘central place'in the Middle Ages. Notably, the volume includes a detailed topographical and epigraphical analysis of its Jewish cemetery, the patronage of arts and architecture by its Syuni and Ōrbēlean princes, its tri-lingual grave and its significance, as well as a full collection of Yeghegis'Armenian epigraphic corpus accompanied by its first English translation. This reevaluation not only enhances our appreciation of Yeghegis'monuments'artistic prominence, long recognized as key specimens of medieval Armenian architecture, but also illuminates on its manifold linguistic, religious, and cultural landscape.